Two Metagenome-Assembled Genomes of Hydrogen-Dependent Methanomassiliicoccales Methanogens from the Zoige Wetland of the Tibetan Plateau - Yun, Juanli (Microbiol Resour Announc, 2021)
Wetlands in the Tibetan Plateau play a crucial role in global carbon cycling. Here, we report the metagenome-assembled genomes (MAGs) of two hydrogen-dependent methanogens from the Zoige wetland of the Tibetan Plateau. The novel species belong to Methanomassiliicoccales, the seventh euryarchaeal methanogenic order.